ANALYSIS OF PROFESSIONAL ETHICS VIOLATIONS IN NOTARY PRACTICE CASE STUDY IN KISARAN CITY - Nurwandri, Andri; Nurasiah; Halizah, Shelly; Halizah, Rizki (PT. Jurnal Center Indonesia Publisher, 2025)
Violation. Ethics. Profession. Notary Public. can occur. In. Various forms, ranging from non-compliance with obligations to maintain confidentiality, permission from authorities, to making deeds that do not comply with legal procedures. Many factors can trigger this violation, such as a lack of understanding of the code of ethics, economic pressure, and conflicts of interest. The impact of these violations not only harms the image of the notary profession, but also has the potential to reduce public trust in legal institutions as a whole.This research adopts a normative-juridical method, which involves literature study and analysis of secondary data. Data that includes secondary sources such as statutory regulations, scientific journals, research results, and so on is an important reference in understanding the authority of Article 67 paragraph (1) of the Law on the Position of Notaries (UUJN) which states that supervision of notaries is carried out by the Minister. In carrying out this supervision, the Minister formed a Notary Supervisory Council which is tasked with ensuring notary compliance with applicable regulations. Supervising notaries is a Supervisory Council created by the Ministry of Law and Human Rights. This institution consists of the Regional Supervisory Council (MPD), Regional Supervisory Council (MPW), and Central Supervisory Council (MPP).According to I Gede A.B. Wiranata, there are eight factors that can influence the decline in morality in the legal profession. These factors include profession, business orientation in carrying out the profession, lack of social awareness and care, stagnation in the justice system, influence of position, consumer lifestyle, weak faith, and the influence of family characteristics. If a notary is involved in violations such as falsifying client data, making deeds that favor one party, or providing false information to clients, this can threaten his career. The client has the right to report the action to the Honorary Council to provide sanctions to the notary in accordance with the applicable code of ethics. Apart from that, clients can also report these actions to the police, which could potentially result in criminal legal consequences for the notary concerned. Therefore, notaries are obliged to carry out their duties based on a professional code of ethics.In general, the position of a notary is regulated in Law Number 30 of 2004 concerning the Position of Notaries, which has been updated through Law Number 2 of 2014, and based on the guidelines contained in the Notary Code of Ethics prepared by the Indonesian Notary Association (INI) in 2005 and updated in 2015.